Disordered eating & body image of current and former athletes in a pandemic - What can we learn from COVID-19 to support athletes through transitions? - Buckley, G.; Hall, L.; Lassemillante, A.-C.; Belski, R. (Journal of Eating Disorders, 2021)
Background: The COVID-19 pandemic has seen worsened mental health as a result of lockdowns, isolation and changes to sociocultural functioning. The postponement of the Tokyo 2020 Olympics is representative of global cancellations of sporting events, reduced facility access and support restrictions that have affected both current and former athletes psychological wellbeing. This study aimed to determine whether current (n=93) and former (n=111) athletes experienced worsened body image, relationship with food or eating disorder symptomatology during acute COVID-19 transitions. Methods: The study was a Convergent Mixed Methods design whereby qualitative content analysis was collected and analysed simultaneously with quantitative cross-sectional data using the EAT-26 and self-report COVID-19 questions. Data were collected from April until May 2020 to capture data pertaining to transitions related to the pandemic and included individuals across 41 different individual and team sports from club to international competition levels. Results: There was a surge in disordered eating behaviours and cognitions in current and former athletes as a result of the early COVID-19 response. Eating disorders were suggested to occur in 21.1% of participants (18% current athletes n=17, 25% former athletes (n=26). There was a signicant difference between males and females (p=0.018, r=0.17), but interestingly no differences between groups from individual vs team sports, type of sporting category (endurance, antigravitational, ball sport, power, technical and aesthetic) or level of competition (club, state, national or international). 34.8% (n=69) selfreported worsened body image and 32.8% (n=65) self-reported a worsened food relationship directly from COVID-19. Qualitative analysis indicated that disordered eating occurred predominantly in the form of body preoccupation, inhibitory food control, fear of body composition changes and binge eating. Conclusions: This study indicates that transitions in COVID-19 have worsened food-body relationships in current and former athletes and must be treated as an at-risk time for eating disorder development. We suggest that resources are allocated appropriately to assist athletes foster psychologically positive food and body relationships through COVID-19 transitions. This study makes practice suggestions in supporting athletes to manage control, seek support, adapt and accept change and promote connection and variety through athletic transitions.